Redefining Speed and Stability: A Meta Analysis of CI/CD Performance through DORA Metrics - Sugianto (Digitus : Journal of Computer Science Applications, 2025)
Continuous Integration and Delivery (CI/CD) has transformed modern software development, enabling faster, more reliable delivery cycles. This article investigates the impact of CI/CD on software delivery speed and stability through a meta analytical review of benchmark studies and industry metrics, with a focus on the DORA framework’s Four Key Metrics: Deployment Frequency, Lead Time for Changes, Change Failure Rate (CFR), and Mean Time to Recovery (MTTR). Utilizing data from DORA, CircleCI, GitLab, and other industry reports, the study applies systematic methods to compare elite and non elite performance bands. Results indicate that mature CI/CD implementation significantly enhances deployment frequency and reduces lead times, while simultaneously improving system stability through lower CFR and faster recovery times. Elite performers exemplify how frequent, stable deployments can be achieved through automation, observability, and standardized tooling. Industry-wide evidence indicates that these principles are broadly applicable across various organizational contexts. Discussion highlights existing barriers to CI/CD adoption, including legacy infrastructure, cultural inertia, and toolchain fragmentation. To address these, the article emphasizes the role of GitOps and platform engineering in streamlining CI/CD operations. Emerging trends such as AI integration, Software Bill of Materials (SBOM), and advanced observability are also identified as future enablers of delivery excellence. In conclusion, CI/CD maturity is strongly correlated with elite performance in software delivery. DORA metrics offer a reliable framework for assessment and continuous improvement. Organizations seeking to scale their DevOps effectiveness must align their practices with these benchmarks while leveraging emerging tools and cultural strategies to sustain delivery excellence.